Pattern of Dermatologic Disorders in Infants - Hussain, Mahfuza; Yasmeen, BH Nazma; Islam, SM Shaheedul; Amin, Narul; Begum, Jamila (BIRDEM Medical Journal, 2013)
Background: Pattern of skin disorders varies in different ages and in different countries. This pattern also varies among children of different ages. The prevalence pattern reflects socioeconomic, environmental and hygienic condition of a community. Objective: This study was planned to evaluate the magnitude of skin diseases and pattern of various dermatoses among children below one year of age in a major tertiary care hospital in the capital of Bangladesh. Method: A retrospective study was undertaken to determine the pattern of skin diseases during the period of January 2010 to June 2012 at the dermatology outpatient department of a tertiary care pediatric hospital in the capital of Bangladesh. Data were analyzed to determine the pattern of skin diseases in children less than one year of age, seen at the Out Patient Department (OPD) of Dhaka Shishu Hospital (DSH). Results: A total of 36608 cases were seen at the dermatological OPD of DSH out of which 9293 (25.39%) were less than one year of age. The frequency of distribution of dermatological diseases was more in male patients 58.2% than in female patients 41.8%. Neonates were 649 (7%) and rest were infants were 8644 (93%). Eczema was the most common skin disorder (55.41%) followed by impetigo & other bacterial infections (27.55%) and scabies (23.44%). Cutaneous fungal infections were 13.99%, miliaria was 4.9%, erythema neonatorum 4.42%, urticaria was 2.18%, bullous lesions 1.45%, haemangioma 1.17% and pityriasis alba 1.15%. About 16 other dermatological disorders were indentified each of which was less than 1% in distribution. Conclusions: Eczema, superficial bacterial infections, scabies and superficial fungal infections were most common dermatological problem in infants. Birdem Med J 2013; 3(2): 80-84 DOI: http://dx.doi.org/10.3329/birdem.v3i2.17210